STRATEGI AUDITOR DALAM MENDETEKSI FRAUD MANAJEMEN MELALUI ANALISIS POLA KEUANGAN - Inayah Chintaki MZ; Annisa Muthmainnah Ichwan; Syamsuddin; Arifuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines auditors’ strategies in detecting management fraud through the analysis of financial patterns as part of the modern audit process. Management fraud has become increasingly difficult to identify because perpetrators often manipulate financial statements through small but consistent adjustments that appear reasonable. Therefore, auditors need to integrate various analytical techniques, such as trend analysis, financial ratio analysis, and financial pattern analysis, to detect anomalies that may indicate fraudulent activities. This research employs a literature review method by examining recent studies related to fraud patterns, characteristics of financial statement manipulation, and data-driven audit techniques. The findings indicate that abnormal profit patterns, significant discrepancies between earnings and cash flows, inconsistent performance trends, and deviant financial ratios are key indicators of management fraud. Furthermore, advanced analytical procedures based on data analytics enhance auditors’ ability to assess fraud risk in a more comprehensive manner. Substantive testing on high-risk accounts is required to validate initial indications and to ensure the sufficiency of audit evidence. This study contributes by providing a comprehensive understanding of auditors’ strategies in detecting management fraud through a combination of financial pattern analysis and structured audit testing.